Attention bias modification for depression: A systematic review and meta-analysis - Xia, Hai-sha; Li, Yu-xi; Zhang, Qing-yun; Zhong, Dong-ling; Liu, Xiao-bo; Gou, Xin-yun; Fan, Jin; Zhao, Jing; Zhang, Yue; Ai, Shuang-chun; Huang, Jia-xi; Li, Juan; et al. (Frontiers in Psychiatry, 2023)
Background Depression is a mental health disorder characterized by affective, somatic, and cognitive symptoms. Attention bias modification (ABM) has been widely used to treat depression. However, the results seem inconsistent. We conducted a systematic review and meta-analysis to investigate the efficacy of ABM for depression and to explore the optimal protocol of ABM. Methods Seven databases were systematically searched from their inceptions to 5 October 2022 to include randomized controlled trials (RCTs) of ABM for depression. Two independent reviewers selected the eligible articles, extracted data, and evaluated the risk of bias using version 2 of the Cochrane risk-of-bias tool (ROB 2.0) for randomized trials. The primary outcome was the evaluation of depressive symptoms using widely accepted and validated scales. The secondary outcomes included rumination and attentional control. Meta-analysis was conducted by using RevMan (version 5.4) and Stata (version 12.0). Subgroup analyses and meta-regressions were performed to identify the source of heterogeneity. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results A total of 19 trials involving 20 datasets (1,262 participants) were included. The overall risk of bias in one study was rated as low risk of bias, three studies were considered as high, and the remaining studies were some concerns. Compared with attention control training (ACT), ABM had a greater effect in the improvement of depression (SMD = −0.48, 95% CI −0.80 to −0.17, I2 = 82%) and rumination (MD = −3.46, 95% CI −6.06 to −0.87, I2 = 0%). No significant differences were observed in the attentional control outcome between ABM and ACT (MD = 3.07, 95% CI −0.52 to 6.65, I2 = 0%). Subgroup analysis demonstrated that adults exhibited a greater decrease in depression scores than adolescents. ABM using the dot-probe task, training target stimulus presented by face, and training directions by left–right were associated with better antidepressant effects. ABM training delivered in the laboratory tended to yield a better effect than those conducted at home. Sensitivity analysis indicated that the results were robust. The certainty of the evidence for all outcomes was low or very low, and publication bias may exist. Conclusion Due to high heterogeneity and limited studies, not enough current evidence supported that ABM could be an effective intervention to relieve depressive symptoms. More rigorous RCTs are required to verify the benefits and to explore the optimal protocol of ABM training for depression. Systematic Review Registration: [PROSPERO], identifier [No. CRD42021279163].